FOOD ALLERGY: CLINICAL MANIFESTATIONS AND DIETARY APPROACHES IN CHILDREN AND ADULTS - Isroilova Gulsanam Mukhtorjon qizi (Web of Journals Publishing, 2025)
This comprehensive analysis examines the morphometric and histometric alterations observed in placental tissues from women with congenital and acquired heart defects. Through systematic evaluation of villous architecture, vascular density, syncytiotrophoblast thickness, and intervillous space distribution, significant deviations from normal placental development patterns were identified. Women with cyanotic heart disease demonstrated marked increases in villous capillary density and altered syncytiotrophoblast-to-cytotrophoblast ratios, while those with acyanotic lesions showed predominantly vascular remodeling changes. The findings indicate that maternal cardiac status directly influences placental morphogenesis, with implications for fetal growth, oxygenation, and perinatal outcomes. These structural adaptations represent compensatory mechanisms aimed at optimizing maternal-fetal exchange despite compromised maternal cardiovascular function, though they may ultimately contribute to pregnancy complications including intrauterine growth restriction and preterm delivery.
Keywords: Placental morphometry, congenital heart disease, maternal cardiac disease, villous architecture, syncytiotrophoblast, placental vascularization, fetal growth restriction.